2020
DOI: 10.1530/jme-19-0210
|View full text |Cite
|
Sign up to set email alerts
|

Fibroblast growth factor-21 potentiates glucose transport in skeletal muscle fibers

Abstract: Fibroblast growth factor 21 (FGF21) is a pleiotropic peptide hormone that is considered a myokine playing a role in a variety of endocrine functions, including regulation of glucose transport and lipid metabolism. Although FGF21 has been associated with glucose metabolism in skeletal muscle cells, its cellular mechanism in adult skeletal muscle fibers glucose uptake is poorly understood. In the present study, we found that FGF21 induced a dose-response effect, increasing glucose uptake in skeletal muscle fibe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 68 publications
(88 reference statements)
0
10
0
Order By: Relevance
“…In skeletal muscle fibers in vitro, low levels of FGF21 induced glucose uptake mediated by the glucose transporter, GLUT4. These data suggest that muscle contractile activity, known to induce FGF21 production, may improve glucose uptake into muscle via FGF21 signaling (Rosales‐Soto et al, 2020; Tezze et al, 2019).…”
Section: Selected Topics In Genetics Development Regeneration and Dis...mentioning
confidence: 96%
“…In skeletal muscle fibers in vitro, low levels of FGF21 induced glucose uptake mediated by the glucose transporter, GLUT4. These data suggest that muscle contractile activity, known to induce FGF21 production, may improve glucose uptake into muscle via FGF21 signaling (Rosales‐Soto et al, 2020; Tezze et al, 2019).…”
Section: Selected Topics In Genetics Development Regeneration and Dis...mentioning
confidence: 96%
“…FGF21 has been proposed as a novel metabolic regulator given its ability to normalize glucose and lipid metabolism and prevent the development of obesity and diabetes [ 125 ]. Recently, it has been reported that FGF21 regulates glucose uptake through a mechanism mediated by GLUT4 and that is dependent on atypical PKC-ζ- in skeletal muscle [ 81 ]. FGF21 gene therapy in animals receiving a long-term high-fat-diet feeding or in ob/ob mice showed marked reductions in body weight, adipose tissue hypertrophy and inflammation, hepatic steatosis inflammation and fibrosis, and insulin resistance due to the higher expression of FGF21 [ 129 ].…”
Section: Myokines Involved In Glucose Uptake In Skeletal Musclementioning
confidence: 99%
“…In skeletal muscle, FGF21 is synthesised under conditions of stress such as mitochondrial myopathies [38]. Studies have demonstrated its ability to increase insulin sensitivity by increasing glucose uptake in primary human skeletal muscle cells and isolated mouse skeletal muscle [57,58] although there is no evidence that this also occurs in vivo [38].…”
Section: Metabolic Functions Of Fgf21mentioning
confidence: 99%